ANALISIS BAURAN PROMOSI DALAM PEMBELIAN ONLINE (STUDI PADA KANTIN YUANK KOTA BIMA) - Rahma Hasan; Sri Ernawati (Jurnal Ilmiah Satyagraha, 2021)
This Research was conducted based on the problems in the  Bima Town Kantin Yuank which consumers considered lacking in promoting their products so that consumers were less interested in making online purchasess at the Kantin Yuank in Bima town.The purpose of study  to determine how good the promotion mix is in online purchases (a study at the Kantin Yuank in Bima town). This type of research is descriptive. The population used in this study is all consumers who have bought products online from the Kantin Yuank in Bima town whose numbers are not known with certanty (unknown population). the number of samples for descriptive research was 100 respondents using purposive sampling tecnique data collection tecniques used in this research are: validity test, reliability test and t test ( one sample t- test).The research in this study indicate that the promotion mix in online purchases ( study at the Kantin Yuank in Bima town) is more than 70 % of the expected ( good).